“I Am Whatever You Say I Am”: The Social Construction of Identity in Rural Drug-Using Women’s Narratives - Bolton, Amanda (2019)
Previous narrative criminology research has examined how drug users manage their identities through discussions of themselves, while providing little insight into how they manage their identities through discussions of others(McIntosh & McKeganey, 2000; Rødner, 2005; Sandberg, 2009).It is important to consider others because according to many symbolic interactionists (Cooley, 1902; Goffman, 1959; Mead, 1934), identity is a social product that is constructed and maintained through social interaction with others and is based on perceptions of others. Cooley (1902) more specifically argued that one’s primary group (i.e., those that are relationally or proximally close to an individual) are even more crucial in the construction and evolution of identity. While research has shown that such significant others (i.e., family members and intimate partners) are risk (Cohen et al., 2007; Joe, 1996; Semple et al., 2013)and protective (Boyd & Mieczkowski, 1990; Tuten & Jones, 2003; Toray et al., 1991)factors in drug users’ lives, researchers have not explored the role of these individuals in narratives. Utilizing a constitutive view of narrative and discourse-oriented approach, this research examines the stories of rural drug-using women—an often-overlooked group in the field of Criminology. Using data from 40 in-depth interviews, this study explores two key research questions: (1) How do drug-using women construct their identities with narrative? and (2) What roles do significant others (i.e., family members and intimate partners) play in this process? Findings align with notions of symbolic interactionism (Cooley, 1902; Goffman, 1959; Mead, 1934). Specifically, the results revealed that the women in the study were able to socially-construct their identities within the context of narrative. The women utilized “facework” (Goffman, 1959) to construct socially acceptable identities for themselves, while downplaying “spoiled” or discredited images of themselves. In the current study, “facework” came in the form of rationalizations and discourse. The women construct their own identities by utilizing discussion of their family members and intimate partners. They blame these individuals, condemn them, utilize them in the narrative as reasons for their behavior, compare themselves to them, and utilize these individuals in an attempt to normalize their own behavior. By doing so, the women are able to construct alternate identities for themselves. Some of these identities were victimizing (i.e., a naive actor, a “sick” patient, a victim, an actor longing for acceptance) and sought to gain sympathy from the audience by presenting the women as vulnerable. Others were normalizing and sought to present the women as relatable and conventional (i.e., a flawed actor like everyone else, a hardworking caregiver/financial provider, a subjectively “normal” actor, a more “acceptable” methamphetamine user). Implications, contributions, and suggestions for future research are discussed